Multimodal user support in IPS² business model - Gegusch, R.; Geisert, C.; Hoege, B.; Stelzer, C.; Roetting, M.; Seliger, G.; Uhlmann, E. (Cranfield University Press, 2009)
The use models of Industrial Product-Service Systems are based on the idea of offering functionality, availability or results. This paper proposes a concept for multimodal user support in interaction with condition monitoring and knowledge generation, whilst taking knowledge protection into consideration. A shared-vision system connects a less-qualified person with an expert for solving problems collaboratively. The user is instructed via multimodal user interfaces, which require data related to the service design, construction model as well as the current machine condition. Such data is acquired by a process accompanying information system, which deliver information relevant to the required service from sensors.
Organised by: Cranfield University
Keywords: Industrial Product-Service Systems; Shared Vision; Virtual Life Cycle Unit; Knowledge Generation